2011
DOI: 10.1007/s10447-011-9138-0
|View full text |Cite
|
Sign up to set email alerts
|

Creating Cultural Competence: An Outreach Immersion Experience in Southern Africa

Abstract: With disasters on the rise, counselors need to increase their cultural awareness, knowledge, and skills to work with affected communities. This study reports outcomes of a four-week immersion experience in southern Africa with six counselor-trainees. Data sources for this qualitative study were: daily journals and demographic forms. Outcomes suggest that sustained contact with community residents and daily supervision experiences served to improve cultural awareness. Recommendations include pushing through stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
(13 reference statements)
2
12
1
Order By: Relevance
“…For example, Tomlinson-Clarke and Clarke (2010) along with Ishii and colleagues (2009) contended that CI must be of sufficient duration for students to be confronted by and have to respond to the potential culture shock arising from being in another culture. Furthermore, group process and safety have been argued to be the conduit for trainees to work through cultural shock, resistance, and feelings that emerge as a result of being "other" (Barden & Cashwell, 2013;Chung & Bemak, 2002;West-Olatunji et al, 2011). Results from the current study suggest that the length of immersion along with opportunities to process CI experiences may have been factors given that scores in cultural sensitivity all increased but developmental levels Downloaded by [Fudan University] at 20:40 14 May 2015 did not change significantly.…”
Section: Implications For Counselor Educators Andcontrasting
confidence: 53%
See 1 more Smart Citation
“…For example, Tomlinson-Clarke and Clarke (2010) along with Ishii and colleagues (2009) contended that CI must be of sufficient duration for students to be confronted by and have to respond to the potential culture shock arising from being in another culture. Furthermore, group process and safety have been argued to be the conduit for trainees to work through cultural shock, resistance, and feelings that emerge as a result of being "other" (Barden & Cashwell, 2013;Chung & Bemak, 2002;West-Olatunji et al, 2011). Results from the current study suggest that the length of immersion along with opportunities to process CI experiences may have been factors given that scores in cultural sensitivity all increased but developmental levels Downloaded by [Fudan University] at 20:40 14 May 2015 did not change significantly.…”
Section: Implications For Counselor Educators Andcontrasting
confidence: 53%
“…Cultural immersion (CI), "direct, prolonged, in vivo contact with a culture different from that of the counselor trainee" (Pope-Davis & Coleman, 1997, p. 232), has been found effective at increasing cultural competence (Pedersen & Leong, 1997;West-Olatunji, Goodman, Mehta, & Templeton, 2011). Trainees process and debrief their field experiences in group, which is argued to be a critical component of CI (Lassiter, Napolitano, Culbreth, & Ng, 2008;Ribeiro, 2004;Shannonhouse, 2013) and the vehicle whereby trainees increase cultural competence (Abreu, Gim Chung, & Alexander, Kruczek, & Ponterotto, 2005).…”
mentioning
confidence: 99%
“…Previous studies (Goodman & West‐Olatunji, ; West‐Olatunji et al, ) showed that experiential learning and cross‐cultural engagement enhance students' critical consciousness. Goodman and West‐Olatunji () explored cultural development among students who participated in an immersion experience involving a disaster‐response outreach project in New Orleans, Louisiana.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…Additionally, understanding disaster response and crisis intervention as well as principles of social justice are an integral part of professional training for counseling students. Recent counseling scholarship has emphasized the importance of multiculturally competent counselors to meet the growing need of mental health service in the global world (West‐Olatunji et al, ).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation